2020
DOI: 10.25095/mufad.673737
|View full text |Cite
|
Sign up to set email alerts
|

Firma Performansının Kar Dağıtımına Etkisi: Sürdürülebilirlik Endeksine Tabi Firmalarda Değerlendirme

Abstract: Kurumsal sürdürülebilirlik kavramı günümüzde önemi giderek artan tartışma konularından biri haline gelmiştir ve firmaların ekonomik olarak devamlılığını etkileyen bir unsur olarak karşımıza çıkmaktadır. Kurumsal sürdürülebilirlik kavramı üzerine yapılan bu çalışmada Borsa İstanbul Sürdürülebilirlik Endeksi'ne tabi firmaların kar dağıtımı yapma kararları üzerinde firma performansının bir etkisinin olup olmadığı Basit Logistik Regresyon yöntemiyle analiz edilmiştir. Çalışmanın sonucunda özkaynak oranı, stok devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, Akıncı et al (2020) examined stock market prices and concluded that stock market prices decreased as the number of cases increased and stock market prices increased as the number of cases decreased. Bayrakdaroğlu (2010), Duman (2010), Doğru (2011), Çakır, Küçükkaplan (2012, Kısakürek and Aydın (2013), Korkmaz, Karaca (2014), Alfarra (2016), Doğan and Topal (2016), Caba (2017) Şamiloğlu, Öztop andKahraman (2017), Tezcan (2017), Ece and Güner (2018), Erdoğan (2018), Aydın (2019), Taysı (2019), Dozen and Başkan (2020), Şahin (2020), Şen (2020), Aya (2021), Kaya (2021), Alantar (2022), Atar (2022) used return on equity ratios as dependent variables in their studies using panel data analysis method. Bayrakdaroğlu (2010) concluded that free float ratios have an impact on the financial performance of firms, while Duman (2010) found that a reliable information flow ensures that investors focus on long-term investment instead of short-term gains.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Akıncı et al (2020) examined stock market prices and concluded that stock market prices decreased as the number of cases increased and stock market prices increased as the number of cases decreased. Bayrakdaroğlu (2010), Duman (2010), Doğru (2011), Çakır, Küçükkaplan (2012, Kısakürek and Aydın (2013), Korkmaz, Karaca (2014), Alfarra (2016), Doğan and Topal (2016), Caba (2017) Şamiloğlu, Öztop andKahraman (2017), Tezcan (2017), Ece and Güner (2018), Erdoğan (2018), Aydın (2019), Taysı (2019), Dozen and Başkan (2020), Şahin (2020), Şen (2020), Aya (2021), Kaya (2021), Alantar (2022), Atar (2022) used return on equity ratios as dependent variables in their studies using panel data analysis method. Bayrakdaroğlu (2010) concluded that free float ratios have an impact on the financial performance of firms, while Duman (2010) found that a reliable information flow ensures that investors focus on long-term investment instead of short-term gains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taysı (2019) found that intangible assets have a positive and significant effect on the return on equity during the crisis period. Dozen and Başkan (2020) analysed the financial data of 42 companies included in the BIST sustainability index in their study in which the effects of company performance on dividend distribution were examined by logistic regression analysis method. In their study, in which return on equity is included in the dependent variables, it was concluded that increasing the capital ratio and the ability to quickly convert stocks into cash affect the decision of firms to distribute dividends.…”
Section: Literature Reviewmentioning
confidence: 99%